2009
DOI: 10.1556/avet.57.2009.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of traditional and modified (VitMaster) methods of rabbit embryo vitrification

Abstract: In spite of their cryobiological efficacy, minimum-volume vitrification methods suffer from the risk of microbiological contamination and are technically and/or manually demanding. In this study, the effects of a traditional, slightly modified vitrification method and vitrification using supercooled liquid nitrogen (VitMaster) applied for rabbit morula-stage embryos were compared. Embryos were equilibrated in a solution containing 1,2-propanediol (2.72 M) and glycerol (1.36 M) for 7 min and vitrified in 0.25-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2011
2011
2012
2012

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Survival of mouse oocytes after very slow cooling rate (!200 8C/min) with high warming rate (O2000 8C/min) was very high when compared with those cooled very rapidly and warmed slowly. However, we and others (see Table 1) have shown that this is not the case for chilling sensitive oocytes and embryos such as those of bovine, pig, rabbit, and human (Arav & Zeron 1997, Lee et al 2007, Papis et al 2009). …”
Section: Progress In Oocyte and Embryo Cryopreservationmentioning
confidence: 65%
“…Survival of mouse oocytes after very slow cooling rate (!200 8C/min) with high warming rate (O2000 8C/min) was very high when compared with those cooled very rapidly and warmed slowly. However, we and others (see Table 1) have shown that this is not the case for chilling sensitive oocytes and embryos such as those of bovine, pig, rabbit, and human (Arav & Zeron 1997, Lee et al 2007, Papis et al 2009). …”
Section: Progress In Oocyte and Embryo Cryopreservationmentioning
confidence: 65%
“…Σο φαινόμενο αυτό προκαλείται λόγω τθσ μεγάλθσ ποςότθτασ υγροφ και αζρα που βρίςκεται μζςα ςτθν παγιζτα κακϊσ και ςτθ μεγάλθ επιφάνειά τθσ.Θ χριςθ μια ςυςκευισ γνωςτισ ωσ VitMaster παρζχει τθ δυνατότθτα ελαχιςτοποίθςθσ του κερμομονωτικοφ μανδφα που δθμιουργείται γφρω από το δείγμα. Σο ςυγκεκριμζνο ςφςτθμα μειϊνει τθ κερμοκραςία του υγροφ αηϊτου ςτουσ -210°C και με αυτόν τον τρόπο εξαλείφεται ο ςχθματιςμόσ ατμοφ γφρω από τθν παγιζτα(Papis et al, 2009). Ωςτόςο ζνα ακόμθ πρόβλθμα είναι ότι οι κρυοπαγιζτεσ μπορεί να εκραγοφν και το δείγμα να χακεί κατά τθ διάρκεια του άμεςου εμβαπτιςμοφ ςτο υγρό άηωτο ι/και κατά τθν ανακζρμανςθ ςτο υδατόλουτρο.…”
unclassified